PENGEMBANGAN INSTRUMEN ASESMEN HIGHER ORDER THINKING SKILLS (HOTS) BERBASIS LITERASI MATEMATIKA PADA MATERI SPLDV - Nining Setyaningsih; Tatiana Dewi Mukodimah (AKSIOMA: Jurnal Program Studi Pendidikan Matematika, 2022)
Higher Order Thinking Skills (HOTS) questions based on mathematical literacy are a form of questions that are still rarely found in learning in schools. This study has the aim of developing a HOTS assessment instrument based on mathematical literacy in SPLDV material. The research method uses the type of Research and Development (R&D). This study uses the characteristics of an assessment instrument to determine the ability of students in solving HOTS skills questions based on mathematical literacy, and involves students of class VIII D as the research population of 14 students. Data collection techniques include (1) preparation of instruments (2) determining instrument validity, (3) revising validator instruments, (4) applying research instruments through trials, (5) obtaining HOTS test results based on students' mathematical literacy, (6) revising instrument. The results of the validator test on the aspects of material, construction, and language are included in the very feasible category with the acquisition of a mean score of 0.94, 0.75, 0.96, and 0.96. The results of the student response questionnaire obtained quite agree about the statements related to the HOTS SPLDV questions based on mathematical literacy. The average results of the assessment development show the medium category. Based on the results of the study indicate that the development of the assessment instrument is categorized as very feasible for learning. Following up on the research results, the development of the HOTS question instrument based on mathematical literacy contributes to students in the application of contextual life